Development strategies and food and nutrition security in Africa: an assessment - Heidhues, Franz; Atsain, Achi; Nyangito, Hezron; Padilla, Martine; Ghersi, Gérard; Le Vallée, Jean-Charles (International Food Policy Research Institute, 2004)
Momentum is building in and around Africa today for policy action to decisively confront hunger and malnutrition. If we are to succeed, it is vital that food and nutrition security strategies be both sound and able to be implemented. Ultimately, strategies deficient in either of these two areas will be ineffectual. Lessons from past strategies provide a valuable resource in the design of future strategies, yet there is a dearth of programmatic information and rigorous evaluations of the approaches used in the past. With this in mind, the authors of this 2020 discussion paper review the multitude of approaches and strategies for achieving food and nutrition security in Africa within the context of development over the past four decades. They assess the extent to which these plans have been implemented and identify the key constraints and limitations, along with the priority investments needed for more effective design and implementation in the future. -- Foreword by Joachim von Braun, Director General, IFPRI